In Vivo Assessment on Freeze-Cast Calcium Phosphate-Based Scaffolds with a Selective Cell/Tissue Ingrowth - Pejchalová, Lucie; Pejchal, Jaroslav; Roleček, Jakub; Vojníková, Michaela; Chlup, Zdeněk; Mařák, Vojtěch; González-Sánchez, Manuela; Čížková, Jana; Salamon, David (ACS applied materials & interfaces, 2024)
Highly porous bioceramic scaffolds are widely used as bone substitutes in many applications. However, the use of bioceramics is often limited to hard tissues due to the risk of potential soft tissue calcification. A further limitation of highly porous bioceramic scaffolds is their poor mechanical stability, manifested by their tendency to break under stress. In our study, highly porous CaP-based scaffolds were prepared via freeze-casting with longitudinal and oriented pores ranging from 10 to 20 μm and a relative porosity of ∼70%. The resulting scaffolds achieved a flexural strength of 10.6 ± 2.7 MPa, which, in conjunction with their favorable bioactivity, made them suitable for in vivo testing. The prepared scaffolds were subcutaneously implanted in rats for two distinct periods: 6 weeks and 6 months, respectively. The subsequent development of fibrous tissue and involvement of myofibroblasts, newly formed vessels, and macrophages were observed, with notable changes in spatial and temporal distributions within the implantation. The absence of calcification in the surrounding soft tissue, as a result of the narrow pore geometry, indicates the opportunity to tailor the scaffold behavior for soft tissue regeneration.
Keywords: poréznost; Tissue Engineering; freeze-casting; fosforečnany vápenaté; Calcium Phosphates; Male; Porosity; Freezing; potkani Sprague-Dawley; testování materiálů; in vivo; scaffolds; Materials Testing; bioceramics; mužské pohlaví; tissue engineering; tkáňové inženýrství; krysa rodu Rattus; zmrazování; Animals; biokompatibilní materiály; zvířata; Rats; Tissue Scaffolds; calcium phosphates; tkáňové podpůrné struktury; Biocompatible Materials; Rats, Sprague-Dawley